Design and Experimental Verification of a New Type of Refrigerated Vehicle Model - Xia Quangang; Liu Baolin; Song Xiaoyan (Zhileng xuebao)
A new type of refrigerator cabinet with composite phase change materials was designed in this paper. In order to assess the refrigerator heat preservation function. First of all, the three dimensional unsteady phase change heat transfer process with variable heat source was simulated and calculated by ANSYS software. Then the simulation results were verified experimentally with cold storage and transportation of Shanghaiqing（Brassicachinensis L.）, the Chinese vegetable. The results showed that the temperature rise of Shanghaiqing inside the cabinet was delayed when the composite phase change materials was applied. So that adding composite phase change materials can effectively improve the effect of the cold in refrigerated vehicle.